Return to play and career length after anterior cruciate ligament reconstruction among canadian professional football players - Longstaffe, R.; Leiter, J.; Gurney-Dunlop, T.; McCormack, R.; MacDonald, P. (The American Journal of Sports Medicine, 2020)
Background: For many athletes, a tear of the anterior cruciate ligament (ACL) represents a significant injury that requires a prolonged period away from the sport with substantial rehabilitation.